Novel fabrication of functionalized graphene oxide via magnetite and 1-butyl-3-methylimidazolium tetrafluoroborate - Lim, Yih Lim; Mubarak, N. M.; Khalid, Mohammad *; Abdullah, E. C.; Numan, Arshid * (Elsevier, 2018)
The fabrication of functionalized graphene oxide via magnetite (Fe3O4) and ionic liquid into ferrofluid is investigated in this study. Several characterizations of the samples were made via Fourier-transform infrared spectroscopy (FTIR), field emission scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), vibrating sample magnetometer (VSM), and flame atomic absorption spectroscopy (FAAS).